MENINGKATKAN HASIL BELAJAR SISWA MELALUI AKTIVITAS BELAJAR KELOMPOK - Khasanah, Binti Anisaul; Nurmitasari, Nurmitasari (JURNAL e-DuMath, 2018)
ABSTRACTThe purpose of this study is to reveal the differences in student learning outcomes before and after applied in the learning group learning activities through pretest and posttest. Achievement test done twice, in order to determine student learning outcomes before being treated and determine student learning outcomes after being treated through group learning activities. The data analysis technique used is the t-test. Based on observations and data analysis research concluded that the use of group learning activities in learning can improve student learning outcomes. So learning where there are group learning activities can be used as an early alternative to improve student learning outcomes.Â Keywords: Group learning activities, Learning outcomes.